PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA DENGAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL UNTUK KELAS VIII SMP/MTS - Yendri, Yulia; Suanto, Elfis; Heleni, Susda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research was done due to the problem found by the teachers' difficulties in developing learning instruments based on Curriculum 13. It needed certain learning instruments to increase students’ knowledges and makes them able to solve problems in their daily life. This research was purposed to make a syllabus, lesson plan, and LAS by using PBM (Problem Based Method) in System of Two Variable Linear Equations Material for Junior High School Students Grade VIII. It was Research and Development design with 4-D models; defining (pendefinisian); designing (perancangan); developing (pengembangan); disseminating (penyebaran). This research was done until third model because of the financial limit. The instruments used were learning instruments validation paper and questionnaire. Syllabus, leasson plan, and LAS were validated by three validators, then it revised and the researcher did tryout test for a small group (consisted of nine students) and large group (consisted of twenty students) at SMPN 14 Pekanbaru. Based on the analysis result, it showed that the validation for syllabus, lesson plan, and LAS with a Likert scale by average 3.70, 3.80, and 3.77 was valid. Besides, for the questionnaire result showed that 88.3% for small group and 95.2% for large group. Based on analysis result and explanation, it can be concluded that syllabus, lesson plan, and LAS by using PBM (Problem Based Method) in System of Two Variable Linear Equations Material for Junior High School Students Grade VIII is practical and suitable for Junior High School Students Grade VIII.Key Words: Problem Based Method (PBM), Mathematics Learning Instruments, System of Two Variable Linear Equations, Validity and Practicality.